Study Efficiency and Possibility of Biogas Production from Effluent from anaerobic digestion with Glycerol Waste - Srinunsuk, Konkanok; เวชสิทธิ์, Pornwimon; Nuithitikul, Kamchai; Siripattana, Chairat (YRU Journal of Science and Technology, 2022)
Currently, the oil palm products is insufficient for palm oil extraction plants. As a result, the biogas production process is lacking of the feedstock. This research focuses on the efficacy and feasibility of bringing Effluent from anaerobic digestion back to the biogas production process. Glycerol waste was added to the Effluent from anaerobic digestion at different ratios. The results showed that the Effluent from anaerobic digestion/palm oil mill effluent ratio of 80:20 with the addition of 3% glycerol gave the highest methane content in biogas. The highest methane content was 62.09% and the methane yield was 240.17 mL-CH4/g-CODadded. The maximum COD removal at this condition was 76%. This condition was selected for further study in a 10-liter continuous stirred tank reactor (CSTR). At HRT of 25 days, the maximum daily methane production was 8,031 mL-CH4 /day and the cumulative methane production was 145,554 mL-CH4. This was equivalent to the maximum daily methane yield of 668 mL-CH4/g-VSadded. The experimental results from the batch and continuous operations were found to fit the extendend AMCO model as indicated by very good correlation coefficients (R2).